Pemanfaatan Limbah Kertas Semen menjadi Bingkai Cermin yang memiliki Nilai Jual di PT X - Khoirunnisa Dzakia Indrasari; Nunik Andina Rahmawati; Fadelia Sabrina Putri Cantika (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The cement packaging waste (paper sack) and leftover cardboard are types of waste generated from daily work activities at PT X. These wastes were found to be piled up without any proper utilization, thus posing a potential breeding ground for disease vectors and potentially polluting the workplace environment. The socialization activity conducted aimed to provide education and innovation in sanitation technology engineering by utilizing mirror frame products with economic value, applying the 3R principles of reducing, reusing, and recycling. The method was implemented through a socialization activity using a one-on-one approach. An evaluation of increased understanding was conducted using pre- and post-tests consisting of 10 questions. Based on the normality test results, a p-value of 0.600 and 0.124 was obtained, which exceeded the alpha value, indicating that the data followed a normal distribution and could proceed with parametric testing using the Paired Sample T-Test. The p-value or sig obtained was 0.006, which is below the alpha value (0.05), so it can be concluded that h alpha is greater than h0. This means that h alpha is accepted and h0 is rejected, indicating that there is a difference between the pre-test and post-test results.